Progress in the application of Huolong pot comprehensive moxibustion in clinical nursing practice (火龙罐综合灸在临床护理中的应用进展) - LYU Shaohua (吕少华); CHEN Hong (陈宏) (Journal of International Translational Medicine Limited, 2024)
Huolong pot comprehensive moxibustion, which integrates massage, scraping, moxibustion and acupoint, has been widely used in clinical nursing practice. This article summarized and analyzed the application status of Huolong pot comprehensive moxibustion in clinical nursing from the aspects of relieving pain, improving respiratory function, improving digestive function and improving sleep quality, so as to provide a basis for clinical nursing. (火龙罐综合灸集推拿、刮痧、艾灸、点穴于一体, 被广泛应用于临床护理操作中。本文从缓解疼痛、改善呼吸功能、改善消化功能、改善睡眠质量等方面对火龙罐综合灸在临床护理中的应用现状进行总结分析, 为临床护理实践提供参考依据。)